National Student Performance Examination - ENADE and the development of competences in higher education (Research, Society and Development, 2018)
This study aims to understand the evaluation process of the National Student Performance Test (ENADE) in the context of developing skills in vocational training in higher education. It is a proposed reflection that relates the evaluation process of higher education, ENADE in relation to the formation of skills and abilities through the four pillars of education proposed by Delors. The understanding of ENADE as a transforming evaluative instrument in contemporary school, as well as the challenges in the construction of competences in higher education and the need of integration between the processes of evaluation and construction of competences from the four pillars of education are related to this text. Based on the proposed reflection, it is considered that the training of competences brought by Perrenoud together with the proposal of the four pillars of education of the XXI century written by Delors form the basis of the contemporary citizen society, inferring the need for evaluative methods to higher education, in the if the ENADE.